1997
DOI: 10.1104/pp.114.2.475
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Environmental Stress on Biomass Partitioning in Transgenic Tobacco Plants Expressing the Movement Protein of Tobacco Mosaic Virus

Abstract: l h e influence of various environmental factors on biomass partitioning between shoots and roots in transgenic tobacco (Nicofiana fabacum) plants expressing the movement protein (MP) of tobacco mosaic virus (TMV) was investigated. TMV-MP-expressing transgenic plants exhibited a root-to-shoot ratio that was approximately 40% below that of transgenic vector control plants. When transgenic plants expressing the TMV-MP were subjected to water-stress conditions, the root-to-shoot ratio was increased to a value com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 19 publications
(29 reference statements)
1
20
0
Order By: Relevance
“…3 More speci®cally, in tobacco plants it has been demonstrated that the nutritional state, especially the concentrations of N, P and K, can in¯uence the production and distribution of biomass. 4 In addition to these macronutrients, other elements can noticeably alter processes and essential nutrient concentrations in tobacco plants. For example, the micronutrient B 5 and the macronutrient Ca appear to exert a strong in¯uence on these processes and parameters.…”
Section: Introductionmentioning
confidence: 99%
“…3 More speci®cally, in tobacco plants it has been demonstrated that the nutritional state, especially the concentrations of N, P and K, can in¯uence the production and distribution of biomass. 4 In addition to these macronutrients, other elements can noticeably alter processes and essential nutrient concentrations in tobacco plants. For example, the micronutrient B 5 and the macronutrient Ca appear to exert a strong in¯uence on these processes and parameters.…”
Section: Introductionmentioning
confidence: 99%
“…While metabolic changes associated with infection by fungi and bacteria have been widely documented (Bolton, 2009), little is known about the effect of plant viruses on host primary metabolites and the influence of these changes on the onset of infection and symptom expression. Traditionally, most studies were devoted to elucidate how plant viruses interfere with carbohydrate metabolism (Herbers et al, 1996;Almon et al, 1997;Balachandran et al, 1997;Herbers et al, 2000;Shalitin and Wolf, 2000). More recently, the advent of metabolomics has allowed the characterization of plant metabolite profiles thorough the detection of a large number of metabolites in target organs (Lisec et al, 2006;Kim et al, 2010).…”
mentioning
confidence: 99%
“…Decrease in relative water contents (RWC) was also observed (Table 2). Deficiency in water contents causes a decrease in leaf turgor or hydraulic pressure on which various physiological processes and morphological traits depend like as stomatal opening and growth of leaves (Tecsi et al, 1996;Balachandran et al, 1997). Furthermore, the BBTV infection in banana caused a decrease in green pigments such as chlorophyll (Chl) a, b and ab.…”
Section: Resultsmentioning
confidence: 99%
“…Virus-free plants show relatively better vegetative growth in field, but reduce with viral infection due to decreased photosynthetic surface, as well as respiration rate (Balachandran et al, 1997;Guo et al, 2005). In general, the plant growth of virus infected plants is limited because of inhibitions of biological system in communication to growth related metabolic processes.…”
Section: Introductionmentioning
confidence: 99%